17.0k views
2 votes
Consider the equation 3p – 7 + p = 13. What is the resulting equation after the first step in the solution?

User Patridge
by
5.8k points

2 Answers

3 votes

The first step would be to combine like terms which is 3p and p so your equation would look like:

4p - 7 = 13

In the second step you would add 7 to both sides which would give you:

4p = 20

The third and last step would be to divide both sides with 4 which would give you your answer:

p = 5


User Slohrsh
by
6.0k points
3 votes

First p=23 and because if u do the math right that is what u should get

User Sharmin
by
5.8k points